(untitled) (Research, Society and Development, 2021)
Introduction: Infection with the human immunodeficiency virus (HIV) is considered a major problem with regard to public health, as its growing number of cases in the world is alarming. Objective: To analyze the nutritional intake indicated for patients undergoing treatment for HIV / AIDS. Methodology: In order to carry out this study, a research was chosen in the form of an integrative literature review Results and Discussion: The human immunodeficiency virus (HIV) is characterized as a highly lethal disease that can cause irreparable damage to the human being. It is known that the risk of opportunistic infection related to this virus in people infected with it increases as long as the CD4 + count is present. Conclusion: It is recommended that every HIV-infected patient be referred to a nutritionist immediately after the first diagnosis to assess their pro.